Assimilation of oil painting methods as a basis of professional formation of artist-teacher - V.V. Mishurovsky (Освітній вимір, 2006)
The article deals with the mam stages of mastering methods of Oil painting and their role in professional training of Fine Arts Teachers. The author describes the ways of improving the process of teaching painting at the Arts Department.